Elevated microRNA-520d-5p in the serum of patients with Parkinson's disease, possibly through regulation of cereloplasmin expression. (20th November 2018) - Jin, Lirong; Wan, Wenbin; Wang, Lingyan; Wang, Changpeng; Xiao, Jianqiu; Zhang, Feng; Zhao, Jue; Wang, Jian; Zhan, Cheng; Zhong, Chunjiu
Highlights: Serum miR-520d-5p level was elevated in PD patients. In vitro work, miRNA-520d-5p decrease CP gene expression in an astrocyte cell line. Abstract: Iron metabolism dysfunction and redox-active iron-induced oxidative stress in the brain may contribute to the pathogenesis of Parkinson's disease. We have previously demonstrated that reduced serum ceruloplasmin level exacerbates nigral iron deposition in Parkinson's disease, although the underlying cause of the low serum ceruloplasmin level in Parkinson's disease remains unknown. Fluorescent quantitative real-time polymerase chain reaction analysis revealed that patients with Parkinson's disease had higher serum levels of microRNA (miR)-520d-5p than controls ( p  = 0.0011). Patients with Alzheimer's disease or multiple system atrophy did not have significantly elevated miR-520d-5p levels. Expression of miR-520d-5p did not correlate with disease severity or the motor phenotype of Parkinson's disease. Luciferase assays confirmed that miR-520d-5p was associated with ceruloplasmin gene expression, as predicted by the TargetScan tool and miRBase. In vitro experiments showed that miR-520d-5p reduced ceruloplasmin gene expression in the U251 astrocyte cell line. Our data suggest that miR-520d-5p may be a potential regulator of ceruloplasmin gene expression in vitro.